Female life-history parameters in the introduced red king crab (Paralithodes camtschaticus, Tilesius 1815) in the Barents Sea : a study of temporal and spatial variation in three Norwegian fjords. - Hjelset, Ann Merete (University of Tromsø, 2012)
The papers of this thesis are not available in Munin: 1. Hjelset, A.M., Sundet, J.H. and Nilssen, E.M.: 'Size at sexual maturity in the female red king crab (Paralithodes camtschaticus) in a newly settled population in the Barents Sea, Norway', Journal of Northwest Atlantic Fishery Science (2009), 41:173-182. Available at http://dx.doi.org/10.2960/J.v41.m633 2. Hjelset, A.M., Nilssen, E.M. and Sundet, J.H.: 'Reduced size composition and fecundity related to fishery and invasion history in the introduced red king crab (Paralithodes camtschaticus) in Norwegian waters', Fisheries Research (2012), 121–122:73-80. Available at http://dx.doi.org/10.1016/j.fishres.2012.01.010 3. Hjelset, A.M.: 'Red king crab (Paralithodes camtschaticus) recruitment potential in Norwegian fjords' (manuscript) The red king crab (Paralithodes camtschaticus) was deliberately introduced to the Barents Sea by Russian scientists during the 1960s, with the purpose to improve coastal fishery and thus improve the local economy. Since the red king crab was caught for the first time in the Varangerfjorden area, the stock has increased in abundance and expanded westward inhabiting coastal areas along the coast of Finnmark from the Russian border in east to the area around Hammerfest in west. Today the population of red king crab supports a valuable fishery in the Barents Sea, representing an ex-vessel value of 150 million NOK in 2011. Several challenges are related to management of the red king crab, since it is an introduced species. The Norwegian management regime today has two goals, one is to keep a long term harvest within a geographical limited area and the second is to limit further spread of the crab. Basic knowledge is needed to meet both objectives, particularly knowledge on life-history traits. The main study area in this thesis has been three large fjords in Finnmark in northern Norway. There is a historical westward spread of the crab along the Norwegian coast, and it has been present in Varangerfjorden, Tanafjorden and Laksefjorden ...